KEPEMILIKAN MANAJERIAL, NILAI PERUSAHAAN, KEBIJAKAN HUTANG TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Makadao, Indri; Saerang, David P. E. (Universitas Sam Ratulangi, 2021)
This study aims to determine the effect of managerial ownership (X1), firm value (X2), and debt policy (X3) on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange. This study uses quantitative research in the form of financial ratio data derived from annual and published financial reports for the period 2014 to 2018. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange amount 163 companies with 36 samples selected using the purposive sampling method and a total of 180 observations. Hypothesis testing is done by using the multiple linear regression method. The results show that (1) managerial ownership has no significant effect on dividend policy; (2) firm value has a significant positive effect on dividend policy; (3) debt policy has a significant negative effect on dividend policy.